The Health Education on Parenting Patterns in Mother and Toddler Classes Using Android-Based E-Modules - Ratna Dewi, Sri Wulan; Sunarni, Neli; Septiani, Hani (Daarul Ilmi: Jurnal Pengabdian Kepada Masyarakat, 2024)
Introduction: The challenge that Indonesia faces is the large proportion of early childhood, which is 30.83 million people. The government, through the Directorate General of Early Childhood Education and Community Education (Ditjen PAUD and Dikmas), is committed to achieving the Sustainable Development Goals (SDGs) target regarding sustainable development, especially target 4.2, namely the development, care and education of quality early childhood (PAUD). One of the SDGs targets is care. Objective : The purpose of this Community Service activity is to increase the knowledge of mothers who have toddlers about child-rearing patterns. Method : The method used is by providing health education to mothers of toddlers and providing questionnaires to be filled out by the mothers of toddlers. Result : he results of this Community Service Activity are in the form of measuring the knowledge of mothers who have toddlers about childcare patterns. The results are that there is an increase in the average value before being given health education and after being given health education, namely 96 to 99. Conclusion : Based on the analysis and results of the activities, health education using the e-module media of parenting patterns can help improve the knowledge of mothers who have toddlers. This media can also be a reading material for mothers who have toddlers and makes it easier because it is already installed on their Android phones. The Community Service activity plan will be ongoing for the integrated health posts in Linggasari Village.